The Effects of Body-Worn Cameras on Police Activity and Police-Citizen Encounters: A Randomized Controlled Trial - Anthony A. Braga (2018)
Many have suggested that placing body-worn cameras (BWCs) on police officers improves the civility of police-citizen encounters and enhances citizen perceptions of police transparency and legitimacy. In response, many police departments have adopted this technology to address public concerns over the quality of policing in their communities. The existing program evaluation evidence on the intended and unintended consequences of outfitting police officers with BWCs is still developing, however. This study reports the findings of a randomized controlled trial involving more than 400 police officers in Las Vegas, Nevada. We find that officers equipped with body-worn cameras generated fewer complaints and use of force reports relative to officers without cameras. BWC officers also made more arrests and issued more citations than their non-BWC counterparts. The findings of this randomized controlled trial raise the possibility that planning for the placement of BWCs on officers should consider the competing effects of improvement in civilian perceptions of police generated by reductions in complaints and use of force incidents and of public concerns about increased enforcement activity